Боспорская хронология: несколько замечаний - Парфенов, В.Н. (Боспорские исследования, 2009)
The principles of correct translation of dates of the Bosporos era into Christian chronology are stated in the article. If it is a question of dates before Christ an index point of readout should be 298 B.C., whereas while translating dates after a boundary of our era for those dates it is necessary to accept 297 B.C. It is underlined, that it is necessary to consider probable discrepancy of the Bosporos calendar with Roman Julian calendar. The examples of practical application of these principles are given. Appendix contains the tables of translation of dates.